Correlation between body mass index and 25(OH)D levels in pregnant women - Sudarma, Verawati; Liman, Patricia Budihartanti; Istriana, Erita; Hamid Jan B Jan Mohamed; Mediana, Achmad (Indonesian Nutrition Association, 2025)
Background: Vitamin D is a vitamin that has a positive effect on maternal and infant health. The mother's nutritional status affects vitamin D levels, where one of nutritional status is expressed in body mass index (BMI). It has been assumed that BMI has the potential to influence the mother's vitamin D levels. Objective: This study analyzes the correlation between BMI and 25(OH)D levels in pregnant women. Methods: This observational analytical study examines data from the medical records of pregnant women who underwent antenatal examinations at the AMS Clinic Kemang from January 2022 to December 2023. The data analyzed were maternal age, gestational age at the time of vitamin D examination, gestational age at delivery, 25(OH)D levels, and maternal BMI. The Pearson correlation or Spearman Rank test was used in bivariate analysis, with a significance level of p<0.05. Results: The mean maternal age was 33.45±6.24 years, with the median gestational age at the time of vitamin D examination being 6.5 mg. The median gestational age at birth was 39 weeks, with vitamin D levels of 20.8 ± 7.8, and a median BMI of 24.22 kg/m2. Based on the results of the Spearman statistical test analysis, there is a strong negative significant correlation between body mass index and levels of 25(OH)D in pregnant women (r -0.747; p=0.008). Conclusion: Pregnant women's body mass index correlates negatively with levels 25 (OH)D. Therefore, it is recommended that pregnant women maintain a BMI within the normal range.